Предмет: Математика, автор: cifej73274

Решите производную сложной функции

Приложения:

Ответы

Автор ответа: QDominus
2

y = (x + 2) \sqrt[3]{x} = x \sqrt[3]{x}  + 2 \sqrt[3]{x}  =  {x}^{ \frac{4}{3} } + 2 {x}^{ \frac{1}{3} }    \\ y' = ( {x}^{ \frac{4}{3} } )' + 2( {x}^{ \frac{1}{3} } )' =  \frac{4}{3}  {x}^{ \frac{1}{3} }  +  \frac{2}{3}{x}^{ -  \frac{2}{3} }  =  \\  =  \frac{4 \sqrt[3]{x} }{3}  +  \frac{2}{3 \sqrt[3]{ {x}^{2} } }  =  \frac{4x + 2}{3 \sqrt[3]{ {x}^{2} } }


cifej73274: Спасибо что ты есть
Похожие вопросы